Sociology Paradigms for Dynamic Integration of Devices into a Context-Aware System - Kamberov, Rustam (2018)
Kamberov, R., Granell, C. and Santos, V. (2017) Sociology Paradigms for Dynamic Integration of Devices into a Context-Aware System, Journal of Information Systems Engineering & Management, 2:1 (2017), 2. doi: http://dx.doi.org/10.20897/jisem.201702